Organizational Resistance in AI-Driven Transformation:A Case Study of PT. Nusantara Komunika - Rini; Hi Djafar, Susanti; Zannah, Raudhatul; Rahmadani, Ari; Hudaya, Emzita (PT. Hanken Sukses Jaya, 2025)
The rapid advancement of artificial intelligence (AI) and digital technologies has fundamentally reshaped the telecommunications industry. Traditional telecom operators are increasingly pressured to move beyond infrastructure provision and transform into technology-driven organizations. PT. Nusantara Komunika (NK), initiated the NK-Future program to shift toward an AI-based Telco-Tech business model. However, the transformation process encountered significant organizational resistance. This study aims to analyze the sources of resistance during NK’s strategic transformation and to propose appropriate organizational development (OD) interventions. Using a qualitative case study approach, this research applies the Power–Interest Matrix and organizational resistance diagnosis as analytical tools. The findings indicate that resistance emerged from economic insecurity, group inertia, covert resistance, and perceived threats to power and professional identity. The study concludes that technological transformation cannot succeed without parallel human and cultural change. A participative, human-centered OD approach is essential to ensure sustainable digital transformation in legacy organizations.